Countercyclical Risks, Consumption, and Portfolio Choice: Theory and Evidence - Shen, Jialu (Management Science, 2024)
Using a quantitative, calibrated life-cycle model, I show that countercyclical earnings risk affects individual consumption growth, reduces the share of wealth in stocks, and affects savings behavior. Using the Panel Study of Income Dynamics survey, I construct an empirical measure of countercyclical earnings risk and find evidence consistent with the model’s predictions. Specifically, larger downside earnings risk decreases consumption growth, increases left skewness in consumption growth, and reduces the share of wealth in stocks. Furthermore, the consumption effects are substantially more significant for stockholders than for nonstockholders, which arises through heterogeneity in the elasticity of intertemporal substitution. This paper was accepted by Tomasz Piskorski, finance. Supplemental Material: The data and online appendix are available at https://doi.org/10.1287/mnsc.2023.4837 .